2020
DOI: 10.3892/ijmm.2020.4829
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA‑1929‑3p participates in murine cytomegalovirus‑induced hypertensive vascular remodeling through Ednra/NLRP3 inflammasome activation

Abstract: MicroRNAs (miRNAs) play an important role in the development of vascular remodeling in essential hypertension (EH) by mediating the effects of human cytomegalovirus (HCMV) on the vascular system. Therefore, the aim of the present study was to investigate the effects of murine cytomegalovirus (MCMV) infection on blood pressure and vascular function in mice, in order to elucidate the role of miR-1929-3p in this process. For model development, 7-month-old C57BL/6J mice were infected with the Smith strain of MCMV,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…More intriguingly, the increase trend of EDNRA expression has been tested in vascular smooth muscle cells suffered from lipopolysaccharide [37]. Wei Zhou et al have validated that elevation of miR-1929-3p decreases blood pressure and attenuates endothelial cell injury in part by decreasing EDNRA expression in hypertensive vascular remodeling [14]. It has been implicated that increased EDNRA function is deleterious for cystic brosis airway [38].…”
Section: Discussionmentioning
confidence: 99%
“…More intriguingly, the increase trend of EDNRA expression has been tested in vascular smooth muscle cells suffered from lipopolysaccharide [37]. Wei Zhou et al have validated that elevation of miR-1929-3p decreases blood pressure and attenuates endothelial cell injury in part by decreasing EDNRA expression in hypertensive vascular remodeling [14]. It has been implicated that increased EDNRA function is deleterious for cystic brosis airway [38].…”
Section: Discussionmentioning
confidence: 99%
“…More intriguingly, the increase trend of EDNRA expression has been tested in vascular smooth muscle cells suffered from lipopolysaccharide [37]. Wei Zhou et al have validated that elevation of miR-1929-3p decreases blood pressure and attenuates endothelial cell injury in part by decreasing EDNRA expression in hypertensive vascular remodeling [14]. It has been implicated that increased EDNRA function is deleterious for cystic brosis airway [38].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, they found that mice overexpressing miRNA-1929-3p exhibited less vascular remodeling and NLRP3 inflammasome activation. This likely occurred by miRNA-1929-3p mediated suppression of the endothelin A receptor (ETRA) which has been shown to be critical in endothelin-mediated blood pressure changes and inflammasome activation [18,68]. Similarly, it was found that miR155-5p limits oxidative stress and IL-1β in the SHR rat model [69].…”
Section: Regulation Of Il-1β By Ncrnasmentioning
confidence: 98%
“…For instance, recent reports suggest that IL-1β not only participates in the pro-inflammatory response in the vessels, it also influences vascular smooth muscle cell (VSMC) phenotype and functions and vascular remodeling in multiple types of hypertension through inflammatory-dependent or independent mechanisms [16]. In addition, another new avenue of research in this area is related to the regulation of IL-1β by non-coding RNAs (ncRNAs) in hypertension [17,18]. These new findings also suggest that analogous regulatory mechanisms may be involved in the pathogenesis of various hypertensive disorders.…”
Section: Introductionmentioning
confidence: 99%